Long-Term Amelioration Practices Reshape the Soil Microbiome in a Coastal Saline Soil and Alter the Richness and Vertical Distribution Differently Among Bacterial, Archaeal, and Fungal Communities - Sun, Ruibo; Wang, Xiaogai; Tian, Yinping; Guo, Kai; Feng, Xiaohui; Sun, Hongyong; Liu, Xiaojing; Liu, Binbin (Frontiers in Microbiology, 2022)
Globally soil salinity is one of the most devastating environmental stresses affecting agricultural systems and causes huge economic losses each year. High soil salinity causes osmotic stress, nutritional imbalance and ion toxicity to plants and severely affects crop productivity in farming systems. Freezing saline water irrigation and plastic mulching techniques were successfully developed in our previous study to desalinize costal saline soil. Understanding how microbial communities respond during saline soil amelioration is crucial, given the key roles soil microbes play in ecosystem succession. In the present study, the community composition, diversity, assembly and potential ecological functions of archaea, bacteria and fungi in coastal saline soil under amelioration practices of freezing saline water irrigation, plastic mulching and the combination of freezing saline water irrigation and plastic mulching were assessed through high-throughput sequencing. These amelioration practices decreased archaeal and increased bacterial richness while leaving fungal richness little changed in the surface soil. Functional prediction revealed that the amelioration practices, especially winter irrigation with saline water and film mulched in spring, promoted a community harboring heterotrophic features. β-null deviation analysis illustrated that amelioration practices weakened the deterministic processes in structuring coastal saline soil microbial communities. These results advanced our understanding of the responses of the soil microbiome to amelioration practices and provided useful information for developing microbe-based remediation approaches in coastal saline soils.